2015
DOI: 10.4018/ijgcms.2015070103
|View full text |Cite
|
Sign up to set email alerts
|

The Differences between Problem-Based and Drill and Practice Games on Motivations to Learn

Abstract: Two trends can be witnessed in educational game design: Problem-Based Learning and Drill & Practice Training approach. The general assumption appears to favor Problem-Based approach above Drill & Practice, in regard to players' motivation. However, the differences between the approaches are seldom studied. The authors examined the motivational impact of one game consisting of a Problem-Based-, and a Drill & Practice learning mode. The first presents players with an ill-defined problem and offers va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…It should be noted that an educational game always has a flexible component and can therefore be adapted to the desired starting situation (Gödecke, 2022). Furthermore, as described in Boghian et al (2019), the presented game MainKassandra focuses on fun while learning and tries to increase the players' motivation to deal with climate adaptation, which was identified as didactically relevant in the studies by Diab et al (2020) and Deen et al (2015). The respondents consider it very positive when changing methods, plot twists and different learning media (analog and digital) are used, as the study by Scholl (2018) also shows.…”
Section: Learning Environmentsmentioning
confidence: 98%
See 1 more Smart Citation
“…It should be noted that an educational game always has a flexible component and can therefore be adapted to the desired starting situation (Gödecke, 2022). Furthermore, as described in Boghian et al (2019), the presented game MainKassandra focuses on fun while learning and tries to increase the players' motivation to deal with climate adaptation, which was identified as didactically relevant in the studies by Diab et al (2020) and Deen et al (2015). The respondents consider it very positive when changing methods, plot twists and different learning media (analog and digital) are used, as the study by Scholl (2018) also shows.…”
Section: Learning Environmentsmentioning
confidence: 98%
“…In GBL and in the respective game mechanics, the focus is on addressing emotional concepts in learning (Boghian et al, 2019). Using the GBL approach to raise awareness of climate adaptation aims to increase motivation and increase people's engagement in a particular activity (Deen et al, 2015;Diab et al, 2020). The aim is to create an environment where mistakes do not have serious consequences and learning is encouraged (Krouska et al, 2021).…”
Section: Resistance To Changementioning
confidence: 99%
“…It encourages learners to seek their own solution to a given problem. In this kind of learning, learners are given a challenge, they are unaware of the solution and their role is to determine the answer (Deen, Van den Beemt & Schouten, 2015). Three participants indicated that they use more drill and practise because some English FAL concepts require memorisation instead of problem solving.…”
Section: Kolobe and Mihaimentioning
confidence: 99%
“…Members of the millennial generation increasingly show a lack of motivation to learn with classical skill and drill practices (Ryan and Deci 2000;Deen and Schouten 2011) and prefer a more experiential and social approach to learning (Oblinger and Oblinger 2005). They generally spend more time using screen media, distracting them from their studies .…”
Section: State Of the Art In Science Practicementioning
confidence: 99%
“…They generally spend more time using screen media, distracting them from their studies . To encourage more autonomy-supportive educational practice is generally accepted as the best way to create more intrinsically motivated students (Deen and Schouten 2014).…”
Section: State Of the Art In Science Practicementioning
confidence: 99%